Interpersonal skills, effects on self-efficacy, and competencies for job performance: undergraduate perspectives - Magaña Medina, Deneb Elí (Acta Universitaria, 2022)
Empirical studies on competencies for job performance are mostly based on opinions of employers; however, it is important to study the role of students as the fundamental actors in the self-assessment of their training. The objective of the study was to determine the direct effect that interpersonal skills have on academic self-efficacy and job performance skills that undergraduate students perceive they have at a public university in southeastern Mexico. To this end, 1158 undergraduate students from all areas of knowledge at a public university in southeastern Mexico were surveyed. As a result of the analysis, the fit indices of the structural relations model report acceptable values. It is concluded that, by verifying the established hypotheses with empirical data, the proposed theoretical model can be explained.